THE PARADOX OF MUSLIM IDENTITY REPRESENTATION IN COMEDIC CONTENT: A NETNOGRAPHIC STUDY OF STEREOTYPES OF MUSLIM WOMEN ON INSTAGRAM - Tahir, Muhammad; Agustin, Riska Dwi; el-Rumi, Umiarso (Harmoni, 2023)
This article attempts to analyze gender stereotypes that portray Muslim women as subjects of ridicule and mockery on social media, especially on Instagram. These stereotypes depict Muslim women as arrogant, selfish, troublemakers, and unintelligent. Based on this focus, this research aims to interpret gender stereotypes on Instagram through the assimilation of comedic content. The study employs a qualitative approach with netnography to understand and interpret these dynamics. Research data is collected through content observation on Instagram and a review of previous studies. Data analysis is conducted using an interactive data analysis model. The research finds that gender stereotypes in the virtual space stem from paradigmatic social gender biases in the real world. These biases are used as material for designing comedic content on Instagram that mocks and ridicules Muslim women. The economic motives of Instagram account owners primarily drive stereotypes in the virtual space. The representation of Muslim identity depicted is far from gender consciousness. This situation creates a paradox between reinforcing the authenticity of Muslim women and the virtualization of their reality in various activities. Literacy and gender awareness based on the theological values of account owners offer a solution to address the paradox of Muslim identity representation.